Artistic beauty ranges from the functional needto the human desire - Kadhim Lafteh Jabr, Asst. Lecturer (lark, 2026)
Our need for beauty is what drives us to prefer and acquire things, given its inherent function in our daily lives, whether it be tangible or intangible beauty.Beauty has been a fundamental element in the creation of art and the application of human ideas. Therefore, it is essential to understand the transformations in aesthetic discourse across eras and societies to grasp the meaning of a work of art and the purpose of its creation. Throughout history, the perception of aesthetic art has been linked to its function. Socrates believed that beauty lies in the perfect fulfillment of function, while Plato and Aristotle considered it a balance and harmony between the soul and the body, thus giving it an ethical dimension. In the Middle Ages, beauty was associated with religion and abstraction, while in the modern era it has transformed into an aesthetic industry. Today, it is closely linked to the visual pleasure promoted by advertising and consumer culture.
Keywords: Keywords: artistic beauty, need, desire